Behind the veil [videorecording] nuns - Wescott, Margaret; Johansson, Signe (s.n.], 1984)
The history of nuns mirrors the history of all women-in what we are taught about the past, women are almost invisible. Although today's one million nuns outnumber priests two to one, they must struggle to be heard by the all male Roman Catholic hierarchy from which they are excluded.